2016
DOI: 10.1017/s0047279416000659
|View full text |Cite
|
Sign up to set email alerts
|

From National to Sub-National? Exploring the Territorial Dimension of Social Assistance in Italy

Abstract: In countries that have experienced decentralisation processes, the role that central and sub-national authorities play in the governance of some social policies may vary considerably across regions. In Italy, for instance, whereas some regions (and municipalities) have been very active in financing social assistance programmes, others still overwhelmingly rely on resources directly allocated by the central government. This indicates that, in a 'regionalised' system, the development of a sub-national social dim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Lastly, in a hitherto unprecedented effort to assess the incidence of austerity across different policy areas, we also found that, much like national-level dismantling processes (Pierson 1994), healthcare was better protected from cutbacks than social assistance payments or spending on education and regional public administration. This might still be consistent with a "functional" interpretation, since the regional health sector appears more nationally coordinated than other sectors, like social assistance (Vampa 2017). Therefore, regions might have been "forced" to cut elsewhere to maintain minimum health standards guaranteed by the national legislative framework.…”
Section: Discussionmentioning
confidence: 59%
“…Lastly, in a hitherto unprecedented effort to assess the incidence of austerity across different policy areas, we also found that, much like national-level dismantling processes (Pierson 1994), healthcare was better protected from cutbacks than social assistance payments or spending on education and regional public administration. This might still be consistent with a "functional" interpretation, since the regional health sector appears more nationally coordinated than other sectors, like social assistance (Vampa 2017). Therefore, regions might have been "forced" to cut elsewhere to maintain minimum health standards guaranteed by the national legislative framework.…”
Section: Discussionmentioning
confidence: 59%
“…The provision of social service can be used effectively to develop human resources (Kurniawan, 2015). The form of distribution of social assistance can be used in the aspect of fulfilling education development resources (Vampa, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…‘Supply‐side’ explanations focus, instead, on institutional factors: local traditions in welfare policy and their historical continuity on the one hand (Bonoli, Natili, & Trein, 2019; Trydegard & Thorslund, 2010), party politics on the other (Bonoli et al, 2019; Vampa, 2017). Local services may be impermeable to exogenous changes and characterized by institutional stickiness (Pierson, 2001) due to established local traditions and habits.…”
Section: Central‐local Tensions and Local Discretion In Multi‐level Institutional Settings: A Theoretical Discussionmentioning
confidence: 99%